Estudio energético del sistema de suministro eléctrico en la Facultad de CAREN perteneciente a la Universidad Técnica de Cotopaxi. - Muenala Guagalango, Mayra Alejandra (2017)
The project is oriented to the energy study of the "Faculty of Agricultural Sciences and Natural Resources" (CAREN), belonging to the Technical University of Cotopaxi. This is done due to the need to know the current state of the electrical system, since there is evidence of an accelerated increase in electrical demand, due to the increase of classrooms, laboratories and spaces due to learning, which forces the updating of the single- Existing ones. In order to know the current state of the electrical system, data were collected on the energy meters of the transformers of 10 and 45 kVA, with the help of the load analyzer "Fluke 435 Serie II", with the values obtained, the curve Of daily demand, in parallel will be carried out field work tending to verify if the drivers that are in the facilities are the suitable ones, later they are determined the voltage drops to know if those falls are within the limits established by the Regulation ARCONEL 004 / 01. The simulation was performed with ETAP software 12.6.0., Which allowed to analyze the voltage drops in the secondary boards of the Transformers, in addition, it was determined that they incorporated new loads without a previous study in the transformer of 45 kVA that has caused an Imbalance of load between its phases, reason why has caused heating in the conductors.